The effect of corporate social responsibility (CSR), board of directors meeting frequency and foreign ownership on dividend policy - Ariesta Pangestu; Megawati (Financial Management Studies, 2021)
This study aims to analyze the influence of corporate social responsibility (CSR), board of directos meeting frequency and foreign ownership on the dividend policy of LQ45 companies listed on the Indonesia Stock Exchange (BEI) for the 2014- 2018 period. The study is casual research. This research was conducted by using purposive sampling method with 21 samples. Data processing was performed using SPSS 25 with multiple linear regression analysis.The results of this study indicate that corporate social responsibility (CSR) has a significant positive effect on dividend policy. Board of directos meeting frequency has no significant effect on dividend policy and foreign ownership has no significant effect on dividend policy.